Prevalence of Intimate Partner Violence: A Comparative Analysis of a Rural and Urban Area in Ekiti State - Adeoye, Beatrice D.; Adebayo, Olutayo A.; Owoeye, Timilehin Peter (CV. Literasi Indonesia, 2024)
Globally ubiquitous, violence against women is a general threat that is often recognized by the victims' loved ones. Men in positions of authority, acquaintances, lovers, and other companions are all possible abusers. However, women are more susceptible to victimization at the hands of an intimate partner. Because of the topic's delicate nature, intimate partner violence is generally underreported; occurrences of such violence are typically not reported to the appropriate authorities. The study examined the prevalence of intimate partner violence in Ado-Ekiti and Ilogbo Ekiti which is a representation of a rural and urban area in the State. The study was carried out on 400 selected respondents in total, 200 respondents in each of the study areas. Data was collected through semi-structured questionnaires using the purposive sampling technique on 400 married respondents. The findings revealed that one out of every two (56%) respondents in the urban area had experienced intimate partner violence however the same could not be said about the rural area where (28%) had had the experience. The further revealed economic stress to be the most potent factor (70%) causing intimate partner violence in the urban area while patriarchy and rigid cultural practices are most cited (63%) in the rural area. In summary, the findings showed emotional pains as the highest consequence (62.5%) of intimate partner violence in the urban area and deteriorating physical health (68.5%) in the rural area Consequently, the study recommends prompt speaking up by abused persons to relevant authorities; training and re-training of agencies who receive intimate partner violence complaints on globally acceptable gender-based response(s), especially in the rural areas.